Clinical Frailty Scale is a good predictor of mortality after proximal femur fracture A Cohort Study of 30- Day and one- year mortality. (2020) - Narula, S.; Lawless, A.; D'Alessandro, P.; Jones, C. W.; Yates, P.; Seymour, H.
No abstract available